Comorbid Diabetes Mellitus and Hypertension Are Associated with Istithaah Status in Hajj Pilgrims - Elman Boy; Nadia Khoiriyah; Muhammad Budi Aulia; Azzura Sufina Ginting; Muhammad Raka Zaelani Saragih; Sukma Khairunisa (Universitas Muhammadiyah Surakarta, 2025)
Hajj pilgrim health istithaah is empowering the congregation's health through quantifiable physical and mental assessments so that the congregation can carry out their worship by Islamic religious guidance. Indonesian Hajj pilgrims are generally elderly and have a high risk of health problems. Common health problems like hypertension and diabetes mellitus. This study objective to analyze the impact of comorbid diabetes mellitus and hypertension on the health status of Hajj pilgrims. Cross-sectional observational analysis was employed in this study. The subjects used simple random sampling and the number of respondents was 289. Data analysis used statistical analysis tests using SPSS. Univariate and bivariate analyses are used in the data analysis. The results of the bivariate analysis between comorbid diabetes mellitus and istithaah status using Chi-Square test showed that p=0.04 (p<0.05) and Spearman Correlation test showed that p=0.01 (p<0.05). The results of the bivariate analysis between comorbid hypertension and istithaah status using Chi-Square test showed that p=0.01 (p<0.05) and Spearman Correlation test showed that p=0.01 (p<0.05). There is a significant relationship between comorbidities of diabetes mellitus and hypertension with istithaah status among prospective Hajj pilgrims embarking in Medan City, North Sumatra Province in 2024